Federal Spending on Labor Market Programs in Brazil - World Bank (World Bank, Washington, DC, 2021)
The objective of labor programs is to improve the efficiency of the labor market inmatching labor demand with labor supply. One way of doing this is by reducing the costborn by workers during the transition between jobs with unemployment insurance andjob-search support. In Brazil some labor programs have the additional, explicit objectiveof supplementing the income of low-wage workers. The provision of labor programs inBrazil is carried out across different ministries and agencies. The bulk of expendituresare made in the form of unemployment cash benefits. Wage supplements and otheractive labor market programs are administered by the Ministry of Labor. Trainingprograms for the unemployed are financed by the Ministry of Education, while somesmaller social programs with a labor support objective are managed by the Ministry ofSocial and Agrarian Development. This chapter of the expenditure review analyzes the volume, trends and efficiency in labor program expenditures in Brazil. It also benchmarks labor program expenditure against comparable spending indicators from other countries, in terms of their function, magnitude and resource allocation. As part of a public expenditure review, the laborprograms covered in this chapter are those that are financed directly from the FederalGovernment’s budget and tracked in budget execution reports from the BrazilianTreasury. So, for example, the chapter covers programs like the Seguro Desemprego,Abono Salarial and PRONATEC. Government mandated programs that are financed byemployers without going through the state budget, such as the Fundo de Garantia por Tempo de Serviço (FGTS), Salário Família and other programs are not analyzed in terms of expenditure trends. The chapter shows that there is significant scope to improve the efficiency and effectiveness of spending on labor market programs. Brazil’s budget expenditure on labor market programs is lower than in OECD countries, but higher than that of comparable economies in Latin America. Spending is significantly higher when offbudget programs mandated by the federal government are taken into account. Budget allocations are tilted towards 'passive' income support programs, although the share of spending on ‘active’ programs has been rising rapidly in recent years. The lack of emphasis on active labor market support—particularly job search assistance and intermediation—is a weakness that limits the government's ability to respond effectively to rising levels of unemployment and to contain spending on passive labor market support. Furthermore, there is an incoherent overlapping of programs with similar functions which adds to perverse incentive effects and fiscal pressures. Indeed, the adjustment formula and extensive use of the statutory minimum wage as a policy parameter has a ratchet effect on fiscal obligations from across the social protection ‘system’ (including pensions and social assistance). The chapter shows that significant efficiency gains and expenditure savings could be obtained from rationalizing programs with similar functions. The document is a Background Chapter for the report Background Chapter for A fair adjustment : efficiency and equity of public spending in Brazil : Volume 1 – Overview (report no. 121480).